Masculinity and Femvertising: A Qualitative Study of Male Consumers in the Skincare Industry - Fitrien Ayuda; Bayu Fajar Susanto; Abunawas Abunawas; Yuslim Yuslim; Hamsal Hamsal; Hidayat Hidayat (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Femvertising refer to an advertising approach that incorporates feminist-oriented or women-empowerment messages. Although numerous studies explored its impact on female consumers, limited research has examined the role of femvertising as a predictor of male consumer' behavior, (particularly in relation to men's skincare products) and how male lifestyle can be incorporated as a mediating variable in the model. Purpose: In this study, we comprehensive examine previous studies to enhance understanding of more about the influence of femvertising on men's skincare purchase intention toward purchasing skincare and with particular attention to the mediating role of male lifestyle. Design/methodology/approach: This study, conducts a systematic literature review is conducted to synthesize and critically assess existing knowledge on femvertising, male consumer behavior, changing masculine norms and lifestyle factors that influence men's skin-care purchases decisions. Key themes, recurring trends in the literature, and research gaps. Findings: The review suggests that femvertising may shape impact men’s attitudes and purchase intention toward skincare product. Specifically, this relationship appears to be influenced by several factors such as social comparison processes and evolving definitions of masculinity, and shifting standards in men's lifestyles. Related studies indicate that contemporary men often integrate grooming practices with their self-concept, which may enhance the positive relationship among femvertising, hedonic motivation, and purchase intention. Limitations and Directions for Future Research: Prior investigations on femvertising have predominantly focused on male respondents, with particular emphasis on their social class. Future empirical studies should broaden the scope to include a more diverse male population, encompassing varied socioeconomic backgrounds, to develop a comprehensive understanding of how lifestyle factors influence consumption behavior. Additionally, subsequent research could examine relevant constructs as potential mediators within the context of femvertising. Practical Implications: Insight into the social comparison processes elicited by alternative masculinity norms can assist companies in devising more effective femvertising strategies for marketing skincare products targeted at male consumers. Originality/value: This literature review synthesises current scholarship around communication and gendered consumption, offer new perspectives on femvertising and further examines men’s responses to marketing of traditionally feminised products. This study explores masculinity in American cultural contexts, particularly in relation to dominant masculine ideology and evolving lifestyles. This leads to a more sophisticated understanding of how men use the consumption process and identifies potential directions for future research considering the evolving nature of gender roles (as boundaries between masculinity and femininity become increasingly blurred) within marketing and consumer culture.